2023
DOI: 10.1021/jacs.2c11117
|View full text |Cite
|
Sign up to set email alerts
|

Data-Centric Heterogeneous Catalysis: Identifying Rules and Materials Genes of Alkane Selective Oxidation

Abstract: Artificial intelligence (AI) can accelerate catalyst design by identifying key physicochemical descriptive parameters correlated with the underlying processes triggering, favoring, or hindering the performance. In analogy to genes in biology, these parameters might be called “materials genes” of heterogeneous catalysis. However, widely used AI methods require big data, and only the smallest part of the available data meets the quality requirement for data-efficient AI. Here, we use rigorous experimental proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Such surface complexity may be explicitly incorporated to refine the data-driven models in the future, for example, by extracting surface information from experimental spectroscopic data . Recent work showed that the SISSO models can be improved if surface information obtained from in situ XPS measurements was included as input features …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such surface complexity may be explicitly incorporated to refine the data-driven models in the future, for example, by extracting surface information from experimental spectroscopic data . Recent work showed that the SISSO models can be improved if surface information obtained from in situ XPS measurements was included as input features …”
Section: Resultsmentioning
confidence: 99%
“…46 Recent work showed that the SISSO models can be improved if surface information obtained from in situ XPS measurements was included as input features. 47…”
Section: Resultsmentioning
confidence: 99%
“…Neural networks and ensemble‐based methods, for example, offer little insight, [46, 47] but can help bridge the gap between different time and length scales of typical DFT calculations and reactor studies and enable fast screening in catalysts (materials) informatics [5h] . Interpretable ML algorithms, on the other hand, can reveal the physical laws underlying catalyst's properties and enable further development of catalyst systems based on hypotheses that follow from this analysis, which can accelerate catalyst discovery in a more sustainable manner [5a, 34b] . These transparent methods in catalysis informatics [5i] include, for example, tree‐based classification and regression methods [5a, 46] .…”
Section: The Diverse Character Of Catalysis Datamentioning
confidence: 99%
“…For this purpose, it is necessary to conduct systematic studies by using reliable experimental data. Interpretable machine learning can likewise contribute to identify relevant characterization methods [34b] …”
Section: The Current Catalysis Data Infrastructurementioning
confidence: 99%
“…With oxygenates as the target product (C 4 , C 3 ) the electronic properties of the bulk and the surface, as well as the adsorption properties of the catalyst are crucial. 40 Hence, the catalytic functionality of bulk catalysts is determined by the properties of the termination layer, which depends on the bulk composition and is formed under reaction conditions. 24,26,36,[41][42][43] However, the surface can additionally be modified using synthetic methods like atomic layer deposition (ALD).…”
Section: Introductionmentioning
confidence: 99%